2016
DOI: 10.1016/j.meegid.2016.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution of respiratory syncytial virus subgroup A genotype NA1 and ON1 attachment glycoprotein ( G ) gene in central Vietnam

Abstract: We performed molecular evolutionary analyses of the G gene C-terminal 3rd hypervariable region of RSV-A genotypes NA1 and ON1 strains from the paediatric acute respiratory infection patients in central Vietnam during the 2010-2012 study period. Time-scaled phylogenetic analyses were performed using Bayesian Markov Chain Monte Carlo (MCMC) method, and pairwise distances (p-distances) were calculated. Bayesian Skyline Plot (BSP) was constructed to analyze the time-trend relative genetic diversity of central Viet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 50 publications
5
13
1
Order By: Relevance
“…More recently, ON1 has displaced NA1 to become the predominantly circulating RSV-A strain ( Eshaghi et al, 2012 ; Valley-Omar et al, 2013 ; Pierangeli et al, 2014 ; Kim et al, 2014 ), although it does not appear to cause more severe disease than other genotypes ( Panayiotou et al, 2014 ; Viegas, Goya & Mistchenko, 2016 ). Our study confirms findings of previous studies in that NA1 and ON1, but not NA3, are frequently identified in Southeast Asia ( Arnott et al, 2011 ; Yoshihara et al, 2016 ).…”
Section: Discussionsupporting
confidence: 92%
“…More recently, ON1 has displaced NA1 to become the predominantly circulating RSV-A strain ( Eshaghi et al, 2012 ; Valley-Omar et al, 2013 ; Pierangeli et al, 2014 ; Kim et al, 2014 ), although it does not appear to cause more severe disease than other genotypes ( Panayiotou et al, 2014 ; Viegas, Goya & Mistchenko, 2016 ). Our study confirms findings of previous studies in that NA1 and ON1, but not NA3, are frequently identified in Southeast Asia ( Arnott et al, 2011 ; Yoshihara et al, 2016 ).…”
Section: Discussionsupporting
confidence: 92%
“…The RSV strains and S. pneumoniae molecular serotypes identified within this cohort are consistent with global circulation patterns from around the time of the study period [43–45]. RSV genotype GA2 was the most highly prevalent strain, followed by BA and GA5.…”
Section: Discussionsupporting
confidence: 68%
“…The ON1, with a 72 nucleotide duplication in the C-terminal region of the G protein, was first detected in hospitalized children in Ontario, Canada in December 2010 [ 12 ]. Since then the genotype was detected various parts of the world and replaced NA1 [ 14 , 18 , 25 , 28 , 37 , 41 , 42 , 44 47 , 56 59 , 61 67 ]. In Japan, the ON1 strain was first detected in 2012 (this study and Tsukagoshi et al)[ 37 ] but it did not prevail until winter during 2014–2015 season as was shown in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In neighboring China, ON1 was initially detected in February 2011 and became the dominant HRSV-A genotype in December 2013[ 42 ]. Other countries, such as Vietnam, the Philippines, Italy and Kenya, reported that the shift from NA1 to ON1 predominance occurred during the 2012–2013 season, almost one to two years earlier than in Japan and mainland China[ 22 , 44 , 56 , 67 ]. Evolutionary analysis of the ON1 strain suggests that this genotype might have emerged from the Americas, specifically in Panama around 2010 [ 45 ].…”
Section: Discussionmentioning
confidence: 99%